Roles of zakat to eradicate poverty: A case study among poor and needy asnaf in Kuala Lipis / Che Haiqal Farhan Che Harun - Che Harun, Che Haiqal Farhan (Academy of Contemporary Islamic Studies, 2018)
The purpose of this research is to identify the role of the zakat to eradicate poverty among the zakat récipients from the needy and poor in Kuala Lipis, Pahang. Although the zakat collection statistic in increasing in each year and eradicate poverty programs carried out yet the poverty phenomena still in existence. The Islamic Council of Pahang (MUIP) which is responsible in superintending the welfare of the muslim and in preparing various subsidiary schemes to ensure that the poor are aided seemly. The main concern is whether the effective steps taken in decreasing poverty is totally eradicated. Therefore this research is to try to analyze whether aid of zakat can accommodate in asnaf expenses. The population of this research among zakat receipents under the poor and needy asnaf. 60% of the total population has been selected as research sample through purposive sampling technique (Gay,1992). 30 samples which include the village of Kg.Dusun, Kg.Kuala Kechau, Kg.Kuala Lanar and Taman Muhibah Batu 4. To understand poverty the respondent profile are analyze by using the Descriptive Statistic method to explain the criteria of group that are enticed in poverty. The fînding shows four group that need attention with the intention of reducing poverty among the poor and needy asnaf. Resuit show that, the majority of respondents agree with the fact that the role of zakat on asnaf expenses can cover their monthly expenses, help them increase the cost of living or income and meet their basic needs. Then, from the findings show that service quality management zakat distribution unit MUIP is still not satisfactory. Hence, it is suggested that MUIP hâve to improve the distribution method, more visit and investigation asnaf and upholding institution of zakat in global field.